1970
DOI: 10.13057/nusbiosci/n070222
|View full text |Cite
|
Sign up to set email alerts
|

Application of chitosan spraying on acclimatization success of tiger orchid (Grammatophyllum scriptum) plantlets

Abstract: Abstract. Pitoyo A, Hani MR, Anggarwulan E. 2015. Application of chitosan spraying on acclimatization success of tiger orchid (Grammatophyllum scriptum) plantlets. Nusantara . In Indonesia, tiger orchid or anggrek macan (Grammatophyllum scriptum) is one of the orchid species that have been mass propagated with in vitro culture technique. The successful determinant of in vitro culture after planlet formation is acclimatization. Plantlet have faced with absolutely different environmental condition between inside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
(1 reference statement)
0
4
0
2
Order By: Relevance
“…Kananont et al [51] studied the effects of various types of CHT at different concentrations on the seed germination of various orchid species and found that none of the six CHT types tested (CHT polymers: P 70 , P 80 Chitosan is also known to stimulate plantlet growth and development under greenhouse conditions. Pitoyo et al [56] studied the effects of CHT on the growth of Grammatophyllum scriptum plantlets and suggested that CHT had significant effects on some parameters, including plantlet height and leaf length. Kumari et al [57] investigated the effects of different CHT concentrations (2.5, 5, 7.5, and 10 mg•L −1 ) on the growth and development of Dendrobium cv.…”
Section: Chitosanmentioning
confidence: 99%
“…Kananont et al [51] studied the effects of various types of CHT at different concentrations on the seed germination of various orchid species and found that none of the six CHT types tested (CHT polymers: P 70 , P 80 Chitosan is also known to stimulate plantlet growth and development under greenhouse conditions. Pitoyo et al [56] studied the effects of CHT on the growth of Grammatophyllum scriptum plantlets and suggested that CHT had significant effects on some parameters, including plantlet height and leaf length. Kumari et al [57] investigated the effects of different CHT concentrations (2.5, 5, 7.5, and 10 mg•L −1 ) on the growth and development of Dendrobium cv.…”
Section: Chitosanmentioning
confidence: 99%
“…After meristem culture and micropropagation of some cassava varieties [11], the seedlings were acclimatized without taking into account the graduation conditions in acclimatization process, and other environmental and intrinsic factors in plantlets [12]. In fact, the nutrient watering solutions, relative humidity and temperature constitute important factors that determine the acclimatization process [13] [14]. Moreover, the effect of substrates is very decisive in the acclimatization success [15] [16] but few have discussed the use of local products including palm fibers and sawdust instead of peat and vermiculite.…”
Section: Introductionmentioning
confidence: 99%
“…are paracytic; and shaped of guard cells are kidney . The type of stomata of Grammatophyllum scriptum is mostly tetracytic, there are four epidermal cells surrounding by two guard cells (Pitoyo et al 2015). was studied on dermal anatomy of two interesting corticolous orchids from Western Ghats, Cymbidium aloifolium Swart and Luisia birchea (A.…”
Section: Resultsmentioning
confidence: 99%